2008
DOI: 10.1183/09031936.00163507
|View full text |Cite
|
Sign up to set email alerts
|

Periodic leg movements in Cheyne–Stokes respiration

Abstract: Periodic leg movements during sleep (PLMS) are repetitive jerks of the lower limbs. Their occurrence can be isolated or part of various sleep disorders, such as restless legs syndrome (RLS), narcolepsy and obstructive sleep apnoea. Dopamine agonists are very effective in suppressing PLMS in RLS from the first night of administration. PLMS are often associated with cortical and autonomic arousals and may contribute to sleep disruption.Herein, a case of association between PLMS, Cheyne-Stokes respiration (CSR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…It could be hypothesized that RLS is associated only with the more severe cases of OSA that are better predicted by neck circumference, as previously suggested [34]. An association between periodic leg movements and respiratory abnormalities during sleep [35] and the significant role of sympathetic activation in periodic leg movements, a condition associated with RLS, have been previously reported [36]. As expected, in this series, quality of sleep was worse in patients with RLS.…”
Section: Discussionsupporting
confidence: 81%
“…It could be hypothesized that RLS is associated only with the more severe cases of OSA that are better predicted by neck circumference, as previously suggested [34]. An association between periodic leg movements and respiratory abnormalities during sleep [35] and the significant role of sympathetic activation in periodic leg movements, a condition associated with RLS, have been previously reported [36]. As expected, in this series, quality of sleep was worse in patients with RLS.…”
Section: Discussionsupporting
confidence: 81%
“…This deficit in striatal dopamine receptor in obese people could contribute to the observed link between RLS and OSA as most OSA patients are obese. However, other studies 40 have reported that dopamine agonists do not impact the number of PLMS associated with Cheyne‐Stokes breathing, suggesting that primary dopaminergic dysfunction may not play a major role in their physiopathology. In summary, the physiopathology of RLS/PLMS in sleep‐disordered breathing appears to be heterogeneous and complex.…”
Section: Rls/plms and Sleep‐related Breathing Disordersmentioning
confidence: 89%
“…In OSAS patients leg movements typically occur synchronously with breathing resumption at the end of each apnea and CPAP treatment is able to decrease PLMS [141]. Recently, Manconi et al [142] described a case of association between Cheyne-Stokes Respiration (CSR) and PLMS. The authors reported synchronization between PLMS and hyperventilation episodes and leg movements were improved by CPAP treatment instead of dopaminergic drugs.…”
Section: Plms In Different Age Categories In Patients With Sleep Dismentioning
confidence: 98%